Activation of Wnt/β-catenin in neural progenitor cells regulates blood–brain barrier development and promotes neuroinflammation - Dylan J. Sebo; Irshad Ali; Audrey R. Fetsko; Aubrey A. Trimbach; Michael R. Taylor (Scientific Reports)
Abstract The central nervous system (CNS) requires specialized blood vessels to support neural function within specific microenvironments. During neurovascular development, endothelial Wnt/β-catenin signaling is required for BBB development within the brain parenchyma, whereas fenestrated blood vessels that lack BBB properties do not require Wnt/β-catenin signaling. Here, we used zebrafish to further characterize this phenotypic heterogeneity of the CNS vasculature. Using transgenic reporters of Wnt/β-catenin transcriptional activity, we found an inverse correlation between activated Wnt/β-catenin signaling in endothelial cells (ECs) versus non-ECs within these distinct microenvironments. Our results indicated that the level of Wnt/β-catenin signaling in non-ECs may regulate Wnt/β-catenin activity in adjacent ECs. To further test this concept, we generated a transgenic Tet-On inducible system to drive constitutively active β-catenin expression in neural progenitor cells (NPCs). We found that dose-dependent activation of Wnt/β-catenin in NPCs caused severe deficiency in CNS angiogenesis and BBB development. Additionally, we discovered a significant increase in the proliferation of microglia and infiltration of peripheral neutrophils indicative of a stereotypical neuroinflammatory response. In conclusion, our results demonstrate the importance of proper Wnt/β-catenin signaling within specific CNS microenvironments and highlights the potentially deleterious consequences of aberrant Wnt activation.